Effect of music therapy on anxiety in full-term pregnant women - Ji, Chao; Li, Juan; Nie, Qiaole; Wang, Shuo (Frontiers in Psychiatry, 2024)
Objectives To examine the impact of receptive music therapy on maternal anxiety both during and after the process of childbirth. Methods In this experimental study, 217 women were divided into the receptive music therapy and control groups. The first group were exposed to music at intervals of 20 minutes for a duration of 30 minutes during labor. Data were collected using the Pregnant Information Form, the State Anxiety Inventory (STAI), Visual Analogue Scale and Edinburgh postnatal depression scale. Results The pregnant women who participated in the music group exhibited reduced scores of STAI, both during the active time (46.42 ± 11.69 vs. 50.21 ± 11.14, 44.37 ± 10.38 vs. 47.56 ± 11.46, P<0.05) and two hours after giving birth(26.32 ± 6.23 vs. 29.55 ± 8.9, 30.38 ± 7.15 vs. 33.08 ± 9.45, P<0.05). At the first stage of labor, pregnant women in the music group experienced dramatically reduced score of pain in active phase (6.39 ± 1.00 vs. 6.91 ± 0.99, P<0.05) and Edinburgh postnatal depression scale at discharged from the hospital (6.68 ± 3.36 vs. 7.66 ± 3.54, P<0.05). Conclusion Receptive music therapy is effective in reducing pain during labor and anxiety during prenatal and postnatal periods. The use of receptive music therapy in obstetric care can be an effective tool in preventing anxiety-induced complications.